The Determinants of Healthy Food Consumption Behaviour during the Covid-19 Pandemic (Unnes Journal of Public Health, 2022)
This research investigated the determinants of healthy food consumption behaviour (HFCB) during Covid-19 pandemic. More specifically, this research aimed to test the effect of digital health communication media usage, e-health literacy, the perceived threat of Covid-19, perceived benefit of HFCB related to Covid-19, attitude toward HFCB, healthy food extension education intensity, healthy food affordability, and social influences - injunctive norm and descriptive norm – on HFCB simultaneously. The data were collected through a survey with 249 respondents in the Tangerang City, Indonesia. A multiple regressions analysis was conducted to analyse the data. The research results showed that HFCB was significantly and positively influenced by attitude toward HFCB, digital health communication media usage, healthy food affordability, and descriptive norm. This research also revealed that HFCB was significantly and negatively influenced by perceived threat of Covid-19. However, perceived benefits of healthy food consumption, e-health literacy, healthy food extension education intensity, and injunctive norm did not pose an impact on HFCB. Keywords: consumption behaviour, healthy food, Covid-19 pandemic, health education, digital communication